Chick Lit, Chick Magnet, Biker Chick, Hippie Chick: Metaphorical Uses of Chick in Contemporary American English - Mottin, Lívia Pretto; Sarmento, Simone (BELT - Brazilian English Language Teaching Journal, 2011)
Metaphors are not just a poetic or rhetorical tool, they are part of our conceptual system (Lakoff and Johnson, 1980). They allow us to understand one aspect of a concept in terms of another. This paper aims at unraveling how the lexeme chick can be used to refer to the female universe. I first review some literature on metaphors, then, check how the domain of animals can be used to better explain human behavior. Next, I present some data collected in the Corpus of Contemporary American English (COCA) for identifying and interpreting some metaphors of the lexeme chick through a corpus-based analysis. In each subcorpus of COCA, the first 100 random concordance lines were analysed in context in order to check whether the search word was used in its metaphorical or in its literal meaning. The non-literal occurrences were better examined, in order to find out the metaphorical use they represent, to determine the positions the lexeme may occupy in a sentence, and to verify its strongest collocations.